2013
DOI: 10.1159/000353712
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Informing Overweight Individuals about the Role of Genetics in Obesity: An Online Experimental Study

Abstract: Background/Aims: Increasing public awareness of obesity genetics could have beneficial or harmful effects on overweight individuals. This study examined the impact of genetic information on weight-related cognitions as well as interest in personalized genetic information about obesity among overweight individuals. Methods: Online survey respondents (n = 655) were randomly assigned to read either genetic, gene-environment, or nongenetic obesity causal information. Fifty-two percent of the participants were fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 4,034 publications
(10 citation statements)
references
References 181 publications
0
8
0
2
Order By: Relevance
“…Participants were randomly allocated to one of three conditions: (a) reading a half page essay on uncontrollable factors contributing towards obesity, (b) reading a half page essay on controllable factors contributing towards obesity, and (c) control (not required to read anything). Essay information was sourced from the Australian Government Department of Health (2009) and NSW Department of Health (2013) , and partially utilised the weight controllability information by Lippa & Sanderson (2013) . In the uncontrollable condition, the information given showed that the environment (e.g., factors in society such as food prices favouring unhealthy food and advertisements), and not the individual, was to blame for weight and that weight was due to genes (e.g., scientific evidence).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were randomly allocated to one of three conditions: (a) reading a half page essay on uncontrollable factors contributing towards obesity, (b) reading a half page essay on controllable factors contributing towards obesity, and (c) control (not required to read anything). Essay information was sourced from the Australian Government Department of Health (2009) and NSW Department of Health (2013) , and partially utilised the weight controllability information by Lippa & Sanderson (2013) . In the uncontrollable condition, the information given showed that the environment (e.g., factors in society such as food prices favouring unhealthy food and advertisements), and not the individual, was to blame for weight and that weight was due to genes (e.g., scientific evidence).…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies tended to be flawed with many methodological issues noted such as the lack of randomised control designs, pre- and post-intervention measures of prejudice not being assessed, and control conditions not utilised. Some success has been reported in successfully changing participants’ genetic causal beliefs but this change was not followed by a change in prejudice towards obesity ( Lippa & Sanderson, 2013 ). Additionally, beliefs that eating habits and lack of exercise contributed toward obesity have been addressed, with higher levels of prejudice supporting the relationship between controllability beliefs and prejudice towards obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with “unexplained physical symptoms,” comorbidity with depression and anxiety was associated with more psychological, as opposed to genetic, attributions . For obesity, findings regarding the impact of genetic causal attributions have varied, with some studies showing no effect, and others showing an association of genetic attributions with reduced control overeating …”
mentioning
confidence: 99%
“…10 Among patients with "unexplained physical symptoms," comorbidity with depression and anxiety was associated with more psychological, as opposed to genetic, attributions. 11 For obesity, findings regarding the impact of genetic causal attributions have varied, with some studies showing no effect, [12][13][14] and others showing an association of genetic attributions with reduced control overeating. 15,16 In this paper, we investigated the relations of depression, the most frequent psychiatric comorbidity in the epilepsies, 17,18 to the perception that epilepsy has a genetic cause.…”
mentioning
confidence: 99%
“…Instead, it appears that there is something special about the combination of fear and receipt of genomic causal information with respect to body weight that results in a profile of psychological outcomes that could be detrimental to performing health behaviors and/or achieving a healthy weight. With few exceptions (15), previous literature has reported that provision of genetic or genomic information related to body weight does not undercut health behavior (17, 18, 3234). In contrast, the current work demonstrates that genomic information can indeed have such negative effects when it is received in the context of a particular emotional state.…”
Section: Discussionmentioning
confidence: 97%